Main drugs and administration routes used in felines - De Oliveira, Cintia; ., Cintia Ferreira Antunes de Oliveira; ., Emanuely Ramos Tameirão; ., Lucas Wamser Fonseca Gonzaga; ., Luciana de Castro Barcelos; ., Lidiane da Silva Bastos; ., Izabel Tavares; ., Larissa Alexsandra Felix; ., João Vitor Fernandes Cotrim de Almeida; ., Marcos Ferrante (Pubvet, 2022)
For the therapeutic protocols to be properly instituted, it is necessary to correctly understand how they will be applied. This bibliographic review aims to characterize the different administration routes used in feline veterinary medicine. In this way, several examples of drugs used by enteral and parenteral routes will be addressed. Once these particularities are studied, it is possible to understand how each pathway works, a factor that considerably increases the effectiveness of treatments. Due to the administration of drugs through the wrong routes, as well as the therapeutic choice most often inappropriate for this species, many cats end up intoxicating. As a result of their hepatic metabolism deficiency and predisposition to develop kidney disorders, many patients have an unfavourable prognosis and end up dying. For this reason, the objective was to elucidate the different types of drugs used in the feline species, in addition to the different doses and routes of administration that can be used in these animals.